Circ_0016347 modulates proliferation, migration, invasion, cell cycle, and apoptosis of osteosarcoma cells via the miR-661/IL6R axis - Yan Liu; Jianjun Yuan; Quan Zhang; Zhishuai Ren; Guang Li; Rong Tian (Taylor & Francis Group, 2022)
Background Osteosarcoma is a common primary bone tumour in children and adolescents. Circular RNAs (circRNAs) exert vital functions in human diseases, including osteosarcoma. Therefore, we explored the role of circ_0016347 in osteosarcoma. Methods The real-time quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression levels of circ_0016347, microRNA-661 (miR-661), and Interleukin-6 receptor (IL6R) in osteosarcoma tissues and cells. The proliferation of osteosarcoma cells was assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazol-3-ium bromide (MTT) and EdU experiments. The migration and invasion were determined by transwell assay. The cell cycle distribution and apoptosis were assessed by flow cytometry assay. The association relationships among circ_0016347, miR-661, and IL6R were analyzed by dual-luciferase reporter assays. The western blot assay was employed to assay the protein expression. A xenograft experiment was established to clarify the functional role of circ_0016347 inhibition in vivo. Results Circ_0016347 was obviously overexpressed in osteosarcoma tissues and cells compared with control groups. The suppression of circ_0016347 impeded proliferation, migration, invasion, and cell cycle and induced apoptosis in osteosarcoma cells, which was overturned by knockdown of miR-661. Consistently, circ_0016347 knockdown repressed tumour growth in vivo. Moreover, miR-661 directly targeted and inhibited IL6R, and the upregulation of IL6R reversed miR-661-induced effects on osteosarcoma cells. Furthermore, circ_0016347 could regulate IL6R expression through miR-661. Inhibition of circ_0016347 also inactivated the Janus kinase 2 (JAK2)/Transcription 3 (STAT3) signalling pathway in osteosarcoma cells by IL6R. Conclusion Circ_0016347 functioned as an oncogene in osteosarcoma at least in part by the miR-661/IL6R axis and JAK2/STAT3 signalling pathway.